Generalized Analysis of Time Scale Dynamic Lyapunov’s Inequalities by Using Specht’s and Kantorovich’s Ratios - Sahir, Muhammad Jibril Shahab (Sarajevo Journal of Mathematics, 2025)
In this paper, we present extensions of dynamic Lyapunov's inequalities and their reverse versions on time scales by using Specht's and Kantorovich's ratios. Our approach unifies and extends some continuous inequalities and their corresponding discrete and quantum analogues.